Kinerja Dinas Koperasi Usaha Mikro Kecil dan Menengah Dalam Pembinaan Usaha Mikro Kecil dan Menengah di Kota Medan - Putri Hertin Andika Pardede; Februati Trimurni (Kolaborasi : Jurnal Administrasi Publik, 2023)
The Medan City Micro, Small and Medium Enterprises Cooperative Service (UMKM) guide the provision of training, socialisation/counselling and assistance in the form of tools and funds following the needs of the UMKM sector. However, there are problems in UMKM coaching that are carried out, namely the weakness of UMKM data collection, UMKM coaching is still uneven, and there needs to be more assistance for UMKM actors who have received coaching. The research method used in this study is a qualitative descriptive research method. Data collection in this study was carried out by interview, observation, and documentation techniques. The data obtained were analysed using a qualitative organisational performance theory approach proposed by Moeheriono, including effectiveness, efficiency, quality, timeliness, and productivity. The results of this study indicate that the performance of the Medan City Micro, Small and Medium Enterprises Cooperative Service is effective because the coaching objectives have been achieved. Still, it could have been more efficient in terms of funds. The performance of the Medan City Micro, Small and Medium Enterprises Cooperative Service (UMKM) from quality indicators is good regarding transparency, conditional, participative aspects, and the balance of rights and obligations. However, it still needs to improve accountability and equal rights. Its performance has good timeliness and productivity.